2024
DOI: 10.2147/jaa.s461138
|View full text |Cite
|
Sign up to set email alerts
|

Nasal Lavage Fluid Proteomics Reveals Potential Biomarkers of Asthma Associated with Disease Control

Meiping Chen,
Yijun Ge,
Wen Zhang
et al.

Abstract: Little research has explored the proteomic characteristics of nasal lavage fluid from asthmatic patients. This study aims to investigate whether differentially expressed proteins (DEPs) in nasal lavage fluid can serve as a biomarker to differentiate asthma patients from healthy controls (HCs) and to discern between individuals with well controlled and poorly controlled asthma. Patients and Methods: We enrolled patients with allergic rhinitis (AR), asthma, or both conditions, and HCs in this study. We recorded … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 37 publications
0
1
0
Order By: Relevance
“…To our knowledge, throat epithelial cells have not been directly studied in the context of asthma, although a recent study has identified the throat microbiota as a potential biomarker for asthma exacerbations despite continued ICS therapy [29]. The nasal epithelium has been more robustly studied in the context of asthma, with the nasal microbiome, nasal lavage, and nasal brushings all showing potential as asthma biomarkers [30][31][32][33]. It has previously been suggested that nasal epithelial cells isolated from asthmatic patients and cultured ex vivo express greater levels of TSLP following rhinovirus infection as compared to cells from healthy individuals [12].…”
Section: Introductionmentioning
confidence: 99%
“…To our knowledge, throat epithelial cells have not been directly studied in the context of asthma, although a recent study has identified the throat microbiota as a potential biomarker for asthma exacerbations despite continued ICS therapy [29]. The nasal epithelium has been more robustly studied in the context of asthma, with the nasal microbiome, nasal lavage, and nasal brushings all showing potential as asthma biomarkers [30][31][32][33]. It has previously been suggested that nasal epithelial cells isolated from asthmatic patients and cultured ex vivo express greater levels of TSLP following rhinovirus infection as compared to cells from healthy individuals [12].…”
Section: Introductionmentioning
confidence: 99%